Test automation techniques for Boto-Intensive IaC Code. (Manning Publications, 2022)
The author of the LP series "AWS Security: Compliance and Observability" compares the use of declarative infrastructure as code DSL such as CloudFormation versus imperative Boto code development, and demonstrates a spectrum of techniques to support testing Boto-intensive IaC.